Comparison between EWGSOP1 and EWGSOP2 criteria and modelling of diagnostic algorithm for sarcopenic obesity in over 70 years old patients - Vágnerová, Tereza; Michálková, Helena; Dvořáčková, Olga; Topinková, Eva (European geriatric medicine, 2022)
PURPOSE: Sarcopenic obesity (SO) as a new diagnostic entity defined by presence of obesity in combination with sarcopenia represents serious health condition negatively affecting quality of life in old age. Despite the rapidly increasing incidence of SO associated with demographic aging, clear diagnostic criteria for SO have not yet been established. We describe here the applicability of the EWGSOP2 and EWGSOP1 diagnostic criteria in identifying sarcopenia and SO and the development of a refinement algorithm for SO detection. METHODS: In total 156 subjects were pre-screened, 126 had a complete dataset and were included, 20.6% (n = 26) were men and 79.4% (n = 100) women, mean age 81 ± 6.3 years in tertiary hospital, Prague, Czech Republic. Testing of physical performance (hand-grip test, 400 m walk test, chair stand test, gait speed), anthropometric measures and SARC-F, SPPB and MNA-SF were used to determine physical, functional, and nutritional status, while muscle mass and fat mass were measured by DXA scans to confirm sarcopenia and SO diagnosis. RESULTS: The prevalence of sarcopenia (BMI adjusted ALM < 0.789 for men, < 0.512 for women) was 26.2% (n = 33), SO in 20.6% (n = 26). 78.8% of all sarcopenic subjects fulfilled the criteria of SO (FM > 27% for men and > 38% for women; waist circumference > 90 cm for men and > 85 cm for women). EWGSOP1 criteria for diagnosing sarcopenia showed better sensitivity of 97.0% than the EWGSOP2 66.7%, while specificity reached 100% for both criteria. According to DXA measurement, EWGSOP1 identified 3.0% cases (1 out of 33) as false negative meanwhile EWGSOP2 identified 33.3% cases as false negative and this difference was statistically significant (McNemar's test, p < 0.001). An algorithm for SO was developed (which uses sex, BMI, height, waist circumference and SPPB) with sensitivity and specificity of 88.5 and 91.0%, respectively. CONCLUSION: High prevalence of obesity among elderly people and rather low sensitivity of current diagnostic criteria for SO call for ongoing research. Broader international consensus for SO diagnostic criteria, screening and diagnosis algorithm are crucial for early detection of SO in older people in clinical practice so that optimal multi-component therapy can be initiated.
Keywords: síla ruky; Hand Strength; Female; ženské pohlaví; Obesity; kvalita života; lidé; Aged, 80 and over; Algorithms; obezita; Male; Aged; Sarcopenia; algoritmy; senioři nad 80 let; senioři; mužské pohlaví; sarkopenie; Quality of Life; Humans